2012
DOI: 10.1504/ijarge.2012.050326
|View full text |Cite
|
Sign up to set email alerts
|

The effect of food-price movements on African households

Abstract: In this paper, we aim to assess households' vulnerability to food-price increases in four countries in sub-Saharan Africa. We use two established indicators of sensitivity to food price changes -one measuring the share of income spent on food, the other measuring net sales of food compared to total expenditures. In contrast to earlier studies, we look at all food items and not just one or a few staple foods and find that the exclusion of non-staple foods has a significant impact on the results. We find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Similarly, Bryngelsson and colleagues have expanded Jayne et al ’s analysis using the 2004 KDHS and by including all foods, and not just the main staples (Bryngelsson et al 2012). They found that 87% of the rural population are net buyers of food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Bryngelsson and colleagues have expanded Jayne et al ’s analysis using the 2004 KDHS and by including all foods, and not just the main staples (Bryngelsson et al 2012). They found that 87% of the rural population are net buyers of food.…”
Section: Discussionmentioning
confidence: 99%
“…The poor performance of agriculture, which has not seen significant increases in productivity, and the consequent inability of smallholders to become wealthier in appreciable numbers, is particularly sobering. This appears partly to be due to the low productivity of smallholders in absolute terms – they cannot produce enough to prosper (Jayne et al 2010; Bryngelsson et al 2012). Case studies of social change in agrarian contexts suggest that rural labour markets seems to be fuelling differentiation within villages that benefit only a minority (Mueller 2011; Greco 2015).…”
Section: Tanzania – Inclusive Growth?mentioning
confidence: 99%
“…However how they have done so, when and for whom is difficult to disentangle from these data. As several researchers have observed, where most poor farmers in fact purchase more food than they produce then crop price increases must, logically, increase household expenditure and make people poorer [56][57][58]. Only relatively few farmers who are net food producers will prosper from the higher prices.…”
Section: Drivers Of Changementioning
confidence: 99%
“…After screening the title and abstract for references to the effect of biofuel or bioenergy demand on agricultural commodity markets, 509 records remained. Full-text resources in English (where these could be obtained; 402 records) were then screened again and records kept were those that: (1) contained original research that (2) presented quantitative estimates of how an increased demand for bioenergy affects agricultural commodity prices at the global, regional, or local level. After this screening 83 studies remained.…”
Section: Materials and Methods A Systematic Review Approachmentioning
confidence: 99%
“…(1) consumers (both intermediate and final) respond to higher prices by lowering demand for agricultural commodities, and farmers respond to price increases by (2) taking new agricultural land into production and (3) by intensifying production to increase yields on existing lands. The larger these responses are, the lower the equilibrium price change.…”
Section: Theoretical Framework and Data Gathered From The Studiesmentioning
confidence: 99%